Viral marketing and purchasing decision: Learning from BTS meal - Mutiara Eka Puspita; Nur Afifah (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study aims to determine whether Viral Marketing, Celebrity Endorsers, and Price influence BTS Meal Purchasing Decisions. The sample in this study was 102 respondents, with a sampling technique using Purposive Sampling. The respondent were people who purchased BTS Meal a minimum of once. This research analysis method uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results showed that: 1) there was a strong and significant influence between viral marketing and the purchase decision of BTS Meal; 2) celebrity Endorsement significantly affects the purchase decision of BTS Meal; 3) the price does not significantly affect the purchase decision of the BTS Meal. The result of the Goodness of Fit (GOF) value in this study is 0.509, which means that the model's fit and the study's variables are robust.